Evaluation of floor acceleration demands from the 2017 Mexico City code seismic provisions using a continuous elastic model and records of instrumented buildings. Issue 2 (December 2020) - Jaimes, Miguel A; García-Soto, Adrián D
This study presents an evaluation of floor acceleration demands for the design of rigid and flexible acceleration-sensitive nonstructural components in buildings, calculated using the most recent Mexico City seismic design provisions, released in 2017. This evaluation includes two approaches: (1) a simplified continuous elastic model and (2) using recordings from 10 instrumented buildings located in Mexico City. The study found that peak floor elastic acceleration demands imposed on rigid nonstructural components into buildings situated in Mexico City might reach values of 4.8 and 6.4 times the peak ground acceleration at rock and soft sites, respectively. The peak elastic acceleration demands imposed on flexible nonstructural components in all floors, estimated using floor response spectra, might be four times larger than the maximum acceleration of the floor at the point of support of the component for buildings located in rock and soft soil. Comparison of results from the two approaches with the current seismic design provisions revealed that the peak acceleration demands and floor response spectra computed with the current 2017 Mexico City seismic design provisions are, in general, adequate.